5PSQ-067 Safety profile of pirfenidone and nintedanib in a real life setting: assessment of suspected adverse drug reactions in the Emilia Romagna region, Italy. (24th March 2020) - Pappalardo, F; Pieraccini, F; Gavioli, B; Carnaccini, F; Fantini, L; Rossi, L
Abstract : Background and importance: Idiopathic pulmonary fibrosis (IPF) is a progressive and fatal form of fibrosing interstitial pneumonia with a poor prognosis, characterised by a decline in lung function, reduction in forced vital capacity (FVC), and worsening of dyspnoea and quality of life. Pirfenidone and nintedanib are the only two drugs with antifibrotic effects approved for the treatment of IPF. They both block the receptors of profibrotic growth factors, such as vascular endothelial growth factor (VEGF), platelet derived growth factor (PDGF) and fibroblast growth factor (FGF). Because of their critical safety profile, many patients are forced to have dose reductions or treatment interruption to manage side effects such as gastrointestinal disorders (diarrhoea, nausea and vomiting), bleeding (epistaxis and contusions), liver enzyme elevation, rash and photosensitivity. Aim and objectives: The aim of this study was to evaluate the safety profile of pirfenidone and nintedanib in the real life setting of the Emilia-Romagna region (RER), Italy. Material and methods: We examined all spontaneous adverse drug reaction (ADR) reports for pirfenidone and nintedanib entered into the National Pharmacovigilance Network by RER healthcare professionals and patients from January 2016 to December 2018 and combined these records with consumption data. We compared the ADR/DDDs ratio of the two drugs and characterised the type and rate of ADRs. Results: From January 2016 to December 2018, we found 22 ADR reports for pirfenidone and 19 for nintedanib, with an ADR/DDDs ratio of 1.44 and 8.61, respectively. The most frequent ADRs reported were photosensitivity reactions (50%) for pirfenidone and gastrointestinal disorders (53%) for nintedanib; the rate of hepatotoxicity was similar between the two drugs (18% and 16%, respectively). Three records (16%) about nintedanib concerned lack of efficacy. Conclusion and relevance: Our results showed that nintedanib had a worse safety profile than pirfenidone, even though the reporting rate is higher in the first years of marketing and pirfenidone has been on the market for longer. The safety profile of the two drugs in a real life setting appeared similar to that found in clinical trials, in terms of both incidence and type of ADRs. References and/or acknowledgements: No conflict of interest.